Produção textual discursiva da opinião referente a problemas sociais do aluno de 9º ano do Ensino Fundamental - Oliveira, Taize Grotto de (2018)
This dissertation is situated in the Text and Speech in Oral and Written Modalities research line of the Program of Postgraduate Studies in Portuguese Language at the Catholic University of São Paulo (PUC-SP). Its theme is the opinative construction in dissertation texts produced by students of the 9th grade of Elementary School. The research question is presented as follows: Are the students of the 9th grade of Elementary School able to draw up and express their own opinions or they only repeat opinions of others? The general goal is to contribute to the development of teaching practices for essay writing to elementary school students, in particular, the 9th grade’s students. The specific goals are: 1) to promote the writing of texts that express opinion and identify the difficulties involved in their production; 2) to examine the circumstances giving rise to opinion; 3) to analyze student’s texts that express opinion, designated as “texts points of view”. The research followed the qualitative approach and adopted the theoretical-analytical methodological procedure. The material used in the analysis was collected among students-participants of the 9th grade of Elementary School. The results indicate that the developed activity allowed the students to produce opinion-type texts based on problems that they experienced in their community. The proposal proved to be effective, since the activity made sense to the students, who identified themselves with the themes that based oral and written textual productions. Therefore, adopting meaningful reading and textual production practices enables a broader understanding of the ways in which students look, understand, and express themselves critically in relation to the reality that surrounds them